The Contribution of Islamic Education in Economic and National Development in the Digital Era - Ahadiah Hanum; Holilur Rahman (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
Islamic education has a very significant role in encouraging economic development and strengthening the nation's character in the digital era. This research underscores the importance of integrating moral values such as honesty, justice and responsibility in the Islamic education curriculum to produce individuals who not only have extensive knowledge but are also based on high morality. Islamic economic principles, such as zakat and infaq, act as effective tools for wealth redistribution, which contribute to reducing social inequality and improving people's well-being. Apart from that, Islamic education that is adaptive to technological developments encourages innovation that supports the digital economy and the development of the halal industry. Therefore, Islamic education not only makes a significant contribution to spiritual and moral aspects, but also plays an important role in economic progress and sustainable national development.